Association of genetically instrumented HMGCR inhibition with the therapeutic role of prostate cancer: a Mendelian randomization study and supporting in vitro experiments - Hao, Xiaojie; Mu, Jingjun (Frontiers in Pharmacology, 2026)
BackgroundThe role of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), which is one of the primary targets of statin drugs, in prostate cancer (PCa) remains controversial. This study aimed to investigate the causal relationship of genetically instrumented HMGCR inhibition with the therapeutic role of PCa through Mendelian randomization (MR) and validate the findings by cell experiments.MethodsWe selected single nucleotide polymorphisms (SNPs) associated with statins use by targeting HMGCR. We used three genome-wide association studies (GWASs) datasets for PCa: PCa (GWAS ID:ieu-b-85, Sample size = 140,254), PCa (GWAS ID:ieu-b-4809, Sample size = 182,625), PCa (GWAS ID:ebi-a-GCST006085, Sample size = 140,254). The inverse variance weighted (IVW) method served as the primary MR approach to validate the suitability of the selected SNPs and to explore the causal relationship between statins use and PCa. To assess the robustness of the MR findings, a comprehensive sensitivity analysis, steiger directionality tests and colocalization analyses were performed. Finally, we validated the MR findings by treating two PCa cell lines with Atorvastatin.ResultsWe ultimately selected 7 SNPs associated with HMGCR. The IVW results indicated that HMGCR inhibition decreased the risk of PCa. Per 1 standard deviation (SD, mg/dL) decrease in low-density lipoprotein cholesterol (LDL-C) was associated with a 16.7% reduction in PCa risk: PCa (GWAS ID: ieu-b-85, Sample size = 140,254) (odds ratio (OR) = 0.833; 95% confidence interval (CI) = 0.726–0.954; P-adjusted = 0.014); Per 1 SD (mg/dL) decrease in LDL-C was associated with a 1.5% reduction in PCa risk: PCa (GWAS ID: ieu-b-4809, Sample size = 182,625) (OR = 0.985; 95% CI = 0.973–0.998; P-adjusted = 0.023) and 16.2% reduction in PCa risk: PCa (GWAS ID: ebi-a-GCST006085, Sample size = 140,254) (OR = 0.838; 95% CI = 0.734–0.956; P-adjusted = 0.014). Results of sensitivity analysis showed MR finding was robust. However, our colocalization results indicated that no shared genetic variants were found in the HMGCR region. Results of cell experiments also demonstrated that statins use could promote apoptosis of PCa cells.ConclusionHMGCR inhibition reduces the risk of PCa, and this protective effect is independent of its lipid-lowering action. Our findings provide strong genetic support for initiating RCTs to investigate the therapeutic potential of statins for partial PCa patients.